(untitled) (Lafia Journal of Scientific and Industrial Research, 2026)
The research investigates the structural, elastic and mechanical characteristics of lead-free cubic CsGeF3 perovskite under density functional theory (DFT) through combined Quantum Espresso and Thermo_PW computational techniques. The researchers conducted three exchange-correlation functional tests (PZ, PBE, and WC) to determine lattice parameter optimization, elastic constant computation and mechanical stability assessment. The research showed that optimized lattice constants achieved results which closely aligned with existing theoretical data. The material’s mechanical stability is demonstrated by its predicted elastic constants which require cubic crystal structures to maintain structural integrity. The evaluation of material’s mechanical properties used Young’s, Shear modulus, and Bulk moduli, Poisson’s and Pugh’s ratio, machinability index, Vickers hardness test and anisotropy factor measurement. The study found that CsGeF3 can withstand compression while displaying ductile behaviour in certain operational situations. The comprehensive study shows that CsGeF3 functions as a lead-free perovskite which shows potential in optoelectronic devices and solar energy harvesting technologies.